Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.6 Implicit Differentiation - 2.6 - Page 168: 59



Work Step by Step

$x^2y^2+xy=2\\ 2x^2yy'+2y^2x+xy'+y=0\\ 2x^2yy'+xy'=-2y^2x-y\\ y'(2x^2y+x)=-2y^2x-y\\ y'=\frac{-2y^2x-y}{2x^2y+x}\\ y'=\frac{-y(2yx+1)}{x(2xy+1)}\\ y'=-\frac{y}{x}$ In order to find the points where the gradient is $-1$, we equal $-1$ to $y'$ $-1=-\frac{y}{x}\\ y=x$ Then we equate $x=y$ to the curve $y^2y^2+yy=2\\ y^4+y^2=2\\ y^2(y^2+1)=2\\ y=1\Longrightarrow x=1\\ y=-1\Longrightarrow x=-1$ Therefore, $(1,1); (-1,-1)$ are the points where the gradient of the tangents is -1.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.